2018
DOI: 10.1111/plb.12838
|View full text |Cite
|
Sign up to set email alerts
|

Water relations in silver birch during springtime: How is sap pressurised?

Abstract: Positive sap pressures are produced in the xylem of birch trees in boreal conditions during the time between the thawing of the soil and bud break. During this period, xylem embolisms accumulated during wintertime are refilled with water. The mechanism for xylem sap pressurization and its environmental drivers are not well known. We measured xylem sap flow, xylem sap pressure, xylem sap osmotic concentration, xylem and whole stem diameter changes, and stem and root non-structural carbohydrate concentrations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…This shrinkage would result from cell volume change due to water release and/or cell wall shrinkage due to adhesive forces between water and the surfaces of the water transporting conduits (Rosner, Karlsson, Konnerth, & Hansmann, 2009). Indeed, daily sapwood shrinkage has been observed in several angiosperm trees (Hölttä et al, 2018;Lintunen, Lindfors, Nikinmaa, & Hölttä, 2017;F. C. Scholz et al, 2008;Sevanto, Hölttä, & Holbrook, 2011), although F. C. Scholz et al (2008) found no correlation between WD and diurnal sapwood shrinkage across six species.…”
Section: Day Capacitance and Its Structural Correlatesmentioning
confidence: 99%
“…This shrinkage would result from cell volume change due to water release and/or cell wall shrinkage due to adhesive forces between water and the surfaces of the water transporting conduits (Rosner, Karlsson, Konnerth, & Hansmann, 2009). Indeed, daily sapwood shrinkage has been observed in several angiosperm trees (Hölttä et al, 2018;Lintunen, Lindfors, Nikinmaa, & Hölttä, 2017;F. C. Scholz et al, 2008;Sevanto, Hölttä, & Holbrook, 2011), although F. C. Scholz et al (2008) found no correlation between WD and diurnal sapwood shrinkage across six species.…”
Section: Day Capacitance and Its Structural Correlatesmentioning
confidence: 99%
“…Springtime stem pressure in Betula pendula is most strongly correlated with temperature, peaking at mid‐day. Xylem sap osmotic pressure in one study was small compared with total xylem pressure and showed little diurnal variation (Hölttä et al ., 2018), but vertical gradients of sugar concentrations were found in birch sap during leaf emergence (Westhoff et al ., 2008), leaving it open to whether osmotic forces play a role for positive pressure in birch. In walnut, xylem pressure was closely correlated with soil temperature and xylem sap osmolarity, and the pressure appeared to originate mainly in the roots (Améglio et al ., 2001).…”
Section: Seasonal Root and Stem Pressure Before Leaf‐out In Deciduousmentioning
confidence: 99%
“…Positive pressure in xylem, which we define as above atmospheric pressure, can potentially occur in roots, stems, rhizomes, and even in leaves, but in the published literature it is generally referred to as ‘root pressure’ even if the source of the pressure is undetermined. For a long time, positive pressure in xylem has been viewed as relative unimportant compared with transpiration‐driven water transport under negative pressure via the cohesion–tension mechanism (Askenasy, 1895; Dixon & Joly, 1895), but there is a resurgence of interest in the topic (Knipfer et al ., 2015; Yang et al ., 2015; Gleason et al ., 2017; Hölttä et al ., 2018). While general reviews of the subject are available (Kramer & Boyer, 1995; Singh, 2016b), the purpose of this review is to discuss positive xylem pressure with a critical assessment of what is known about underlying mechanisms and explore by model calculations what conditions are required for root pressure to occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…xylem sap pressurization [167,168]. The concentrations of the main sugars (glucose 2.5-4.7 and fructose 2.3-4.5 5-8 g L −1 ) of birch sap (Betula pendula Roth.…”
Section: Effects Of Climate Change On Efn-dependent Communitiesmentioning
confidence: 99%